Emotions in Korean Philosophy and Religion Confucian, Comparative, and Contemporary Perspectives - Chung, Edward Y. J.; Oh, Jea Sophia (Palgrave Studies in Comparative East-West Philosophy, 2022)
This pioneering book presents thirteen articles on the fascinating topic of emotions (jeong 情) in Korean philosophy and religion. Its introductory chapter comprehensively provides a textual, philosophical, ethical, and religious background on this topic in terms of emotions West and East, emotions in the Chinese and Buddhist traditions, and Korean perspectives. Chapters 2 to 5 of part I discuss key Korean Confucian thinkers, debates, and ideas. Chapters 6 to 8 of part II offer comparative thoughts from Confucian moral, political, and social angles. Chapters 9 to 12 of part III deal with contemporary Buddhist and eco-feminist perspectives. The concluding chapter discusses ground-breaking insights into the diversity, dynamics, and distinctiveness of Korean emotions. This is an open access book.